Student business wortal – passion or idea at the business? Prospects for the development of BiznesZone.pl - Chlebiej, Joanna (Funkcjonowanie e-biznesu. Zasoby, procesy, technologie, 2015)
Can realization of student passion be transformed into a sound success in business? An answer to this question can be found in the interview with the founder of student's portal BiznesZone.pl as well as in participant's observations which are discussed in this publication. The article presents the business model, opportunities and areas for cooperation with editors and businesses, as well as methods of promotion and recruitment of new contributors. The stakeholders analysis has helped to reveal main directions of promotion and public relations efforts. In the interview, the founder of BiznesZone.pl describes the origins of his business, the strategy which he and his companion have chosen as well as goals, vision and mission of this project. The current level of realization of this strategy is discussed as well. The next section is devoted to the attempt to assess economic potential and prospects for further development of BiznesZone.pl. A SWOT analysis has been performed to find the main strengths, weaknesses, opportunities and threats. Finally, the interview concludes with a few words about the directions of activity in the future.